Pengembangan Karakter Peduli Lingkungan Melalui Metode Bermain Peran pada Siswa Sekolah Dasar - Salsabilla, Hanansya Nur (Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This study focuses on developing environmental care character through role-playing methods among elementary school students. The method is designed to enhance students' understanding and awareness of environmental issues by integrating role-playing into their curriculum. The research involves elementary school students as the main subjects, employing a qualitative approach to collect data through observation, interviews, and document analysis. The findings indicate that the role-playing method is effective in shaping environmental care character among students, increasing their participation in environmental conservation activities, and enriching their learning experiences. This study contributes to the development of learning strategies that emphasize the formation of environmental care character from an early age, empowering students to become responsible agents of change for the future environment. The research provides a foundation for implementing similar methods in the context of character education at the elementary school level.